Study on Radio Frequency Identification (RFID) Implementation for Effective Materials Tracking at Congested Construction Site - Yuan Shien, Loh; Kasim, Narimah; Zainal, Rozlin; Shareh Musa, Sharifah Meryam; Mohd Noh, Hamidun (Research in Management of Technology and Business, 2021)
Due to the population of Malaysia rise every year and the demand for property increase so the construction industry in Malaysia growth rapidly. Some of the states in Malaysia that occur urbanization lead the construction project in the current state increase and cause limited space for the construction project. Limited space of construction site directly affects to the congested construction site and bring delay issues. One of the factors of delay issues is the materials tracking problem at the congested construction site. Many types of materials tracking system implementation at the congested construction site but Radio Frequency Identification (RFID) seem more prominent. Even though RFID is established in the market but there are still challenges in the implementation of this technology. Therefore, this study seeks to identify the effectiveness of materials tracking at the congested construction site with the potential implementation of RFID. The research methodology adopted in this research is quantitative methods and the instrument that use to collect the data is questionnaires. The location of this research was conducted at Johor and the respondents of this research are G7 contractors. The results of this study show that RFID has the potential in providing convenient materials tracking to reduce the cost of materials wastage. The biggest challenge of RFID implementation is the financial support due to the cost of technology. In conclusion, the research provides substantial knowledge of effective materials management with RFID implementation in material tracking at the congested construction site.